Cobalt hydroxide and its preparation method and application

The preparation of cobalt hydroxide nanosheet-like structures by using cobalt salt, NaOH and surfactant precipitation reaction in the reaction device was solved, and the stability of the cathode material and the cycling performance of the battery were improved.

CN119143192BActive Publication Date: 2025-04-22YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411614200.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-04-22
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

When the ternary cathode material is exposed to air, residual lithium reacts with CO2 and H2O to form a by-product, hindering the migration of lithium ions and affecting battery safety and cycling performance.

Method used

By performing the precipitation reaction in the reaction device, a soluble cobalt salt, NaOH solution and surfactant are used as precipitant and complexing agent to prepare a cobalt hydroxide nanosheet-like structure for coating the positive electrode material.

Benefits of technology

The thermal stability and structural stability of the positive electrode material are improved, the interface reaction between the positive electrode material and the electrolyte is suppressed, and the cycle stability and capacity retention rate of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143192B_ABST
    Figure CN119143192B_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt hydroxide and a preparation method and application thereof, belonging to the technical field of battery materials. The preparation method comprises: subjecting a soluble cobalt salt solution, a precipitant solution and a complexing agent solution to a precipitation reaction; the precipitant is a NaOH solution; the complexing agent is a surfactant, and the surfactant comprises at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, hexadecyltrimethylammonium bromide, polyoxyethylene polyoxypropylene ether, polyvinyl pyrrolidone and polyethylene glycol. The method is simple to operate and the process is easy to control. By regulating the surfactant, cobalt hydroxide of different sizes and a unique spatially staggered nanosheet structure can be obtained, which is beneficial to improving the utilization rate of active materials, improving the charge and discharge cycle life, the conductivity and charging efficiency of the electrode, etc. Using it as a coating layer can improve the thermal stability and structural stability of the positive electrode material, inhibit the interface reaction between the positive electrode material and the electrolyte, and thus enhance its cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to cobalt hydroxide and a preparation method and application thereof. Background Art

[0002] With the popularity of electric vehicles, the electric vehicle (EV) market is paying more attention to high energy density and low cost lithium-ion batteries (LIBs). Among them, the performance of the positive electrode material plays a vital role in battery performance and cycle life. In comparison, ternary positive electrode material metal oxides have higher energy density and lower raw material cost, and are regarded as ideal positive electrode materials for lithium-ion batteries.

[0003] Although ternary cathode materials can provide ideal energy density, the lithium source is usually in excess relative to the transition metal during the mixed lithium sintering process, which will lead to residual lithium on the surface of the cathode material. Therefore, if the ternary cathode material is exposed to the air, the residual lithium on the surface of the material will react with CO2 and H2O in the air to form byproducts such as lithium hydroxide and lithium carbonate, which will hinder the migration of lithium ions and produce side reactions with electrolytes, polymer binders, etc., and generate gas, which poses a great risk to the safety of the battery.

[0004] In addition, the medium-high nickel ternary cathode material has a higher reversible discharge capacity due to its high nickel content, but its cycle performance is poor. This is mainly caused by the unstable surface properties, structural defects, lithium-nickel mixing, intergranular cracks and micro-strain of the material.

[0005] Therefore, in order to solve the above problems, researchers have proposed many modification strategies, including surface engineering, bulk doping, morphology control, surface coating, etc. At present, common coating compounds mainly include inert compounds such as oxides, fluorides, phosphates, and conductive materials such as carbon-based materials and lithium-containing compounds, while there are relatively few studies on cobalt compounds as surface coatings.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The object of the present invention is to provide a cobalt hydroxide and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0008] The present invention can be implemented like this:

[0009] In a first aspect, the present invention provides a method for preparing cobalt hydroxide, comprising the following steps: subjecting a soluble cobalt salt solution, a precipitant solution, and a complexing agent solution to a precipitation reaction in a reaction device having a base liquid until the particle size grows to a preset particle size;

[0010] The precipitant in the precipitant solution is a NaOH solution; the complexing agent is a surfactant, and the surfactant includes at least one of sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfonate (SDS), dodecyltrimethylammonium bromide (DTAB), hexadecyltrimethylammonium bromide (CTAB), polyoxyethylene polyoxypropylene ether (F127), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG).

[0011] In an optional embodiment, the conditions of the precipitation reaction include: a temperature of 30° C. to 70° C., a stirring speed of 300 rpm to 700 rpm, a hydroxide concentration in the reaction system not exceeding 2.0 mol / L, and a protective atmosphere.

[0012] In an optional embodiment, the concentration of hydroxide in the reaction system is 0.001 mol / L~2.0 mol / L.

[0013] In an optional embodiment, the concentration of hydroxide in the reaction system is 0.02 mol / L~2.0 mol / L.

[0014] In an optional embodiment, the soluble cobalt salt includes cobalt sulfate; the concentration of the soluble cobalt salt solution is 1 mol / L to 3 mol / L;

[0015] and / or, the concentration of NaOH in the precipitant solution is 10% to 50%;

[0016] And / or, in the complexing agent solution, the concentration of the complex is 0.1 g / L to 100 g / L.

[0017] In an optional embodiment, a soluble cobalt salt solution, a complexing agent solution and a precipitant solution are added to the base liquid in parallel, wherein the flow rate of the soluble cobalt salt solution is 1 L / h~30 L / h, the flow rate of the complexing agent solution is 60 mL / h~400 mL / h, and the precipitant solution is used to control the concentration of hydroxide in the reaction system.

[0018] In an optional embodiment, the base liquid is obtained by mixing water and a liquid alkali solution; wherein the volume of water is 30% to 70% of the volume of the reaction container, and the concentration of hydroxide in the base liquid does not exceed 2.0 mol / L.

[0019] In an optional embodiment, the method further comprises: aging and filtering the slurry obtained by the coprecipitation reaction to form a filter cake; centrifugally washing, slurrying and drying the filter cake;

[0020] Among them, the aging time is 2h~6h;

[0021] And / or, the centrifugal washing includes: sequentially performing alkali washing and water washing on the filter cake; wherein the alkali washing includes the following conditions: the alkali washing temperature is 25°C to 100°C, the washing agent used for the alkali washing is 1mol / L to 3mol / L sodium hydroxide; the volume of the washing agent used for the alkali washing is 25L to 200L; the water washing includes the following conditions: the water washing temperature is 70°C to 100°C, and the volume of water used for the water washing is 50L to 400L; in the filter cake after centrifugal washing, the Na content is ≤1000ppm, and the S content is ≤1000ppm;

[0022] and / or, the slurrying time is 0.5h~5h;

[0023] And / or, the drying temperature is 50°C to 120°C, and the material is dried to a moisture content of ≤0.8%.

[0024] In a second aspect, the present invention provides cobalt hydroxide, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0025] In an optional embodiment, the cobalt hydroxide is a nanosheet structure;

[0026] and / or, the average particle size D of cobalt hydroxide 50 0.2μm~5μm.

[0027] And / or, the thickness of the cobalt hydroxide is ≤100 nm.

[0028] In a third aspect, the present invention provides a modified positive electrode material, wherein the modified positive electrode material is obtained by coating the surface of a positive electrode material with the cobalt hydroxide of the aforementioned embodiment.

[0029] In an optional embodiment, the positive electrode material is a nickel-cobalt-manganese ternary positive electrode material.

[0030] In a fourth aspect, the present invention provides a battery having the modified positive electrode material of the aforementioned embodiment.

[0031] The beneficial effects of the present invention include:

[0032] The preparation method of cobalt hydroxide provided by the present invention is simple to operate and the process is easy to control. By continuously feeding wet synthesis, different surfactants are used to obtain cobalt hydroxide products of different sizes and having a nano-sheet structure. In the product, different cobalt hydroxide particles are in a spatially staggered form, which is beneficial to improve the utilization rate of active substances, improve the charge and discharge cycle life, improve the conductivity and charging efficiency of the electrode, etc. Coating the positive electrode material can improve the thermal stability and structural stability of the positive electrode material, inhibit the interface reaction between the positive electrode material and the electrolyte, thereby enhancing its cycle stability, and further improve the specific capacity and capacity cycle retention rate of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a SEM image of the cobalt hydroxide product prepared in Example 1 at a magnification of 50,000 times;

[0035] Figure 2 This is a SEM image of the cobalt hydroxide product prepared in Example 2 at a magnification of 50,000 times;

[0036] Figure 3 This is a SEM image of the cobalt hydroxide product prepared in Example 3 at a magnification of 50,000 times;

[0037] Figure 4 This is a SEM image of the cobalt hydroxide product prepared in Example 4 at a magnification of 50,000 times;

[0038] Figure 5 This is a SEM image of the cobalt hydroxide product prepared in Example 5 at a magnification of 50,000 times;

[0039] Figure 6 This is a SEM image of the cobalt hydroxide product prepared in Example 6 at a magnification of 50,000 times;

[0040] Figure 7 This is a SEM image of the cobalt hydroxide product prepared in Comparative Example 1 at a magnification of 50,000 times. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0042] The cobalt hydroxide provided by the present invention and its preparation method and application are described in detail below.

[0043] The invention provides a method for preparing cobalt hydroxide, which comprises the following steps: subjecting a soluble cobalt salt solution, a precipitant solution and a complexing agent solution to a precipitation reaction in a reaction device with a base liquid until the particle size grows to a preset particle size.

[0044] Wherein, the soluble cobalt salt includes cobalt sulfate. The concentration of the soluble cobalt salt solution can be 1 mol / L to 3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, etc., or other values ​​within the range of 1 mol / L to 3 mol / L.

[0045] The precipitant solution is a NaOH solution. The concentration of NaOH in the precipitant solution may be 10% to 50%, such as 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., or other values ​​within the range of 10% to 50%.

[0046] The complexing agent is a surfactant, and the surfactant includes at least one of sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfonate (SDS), dodecyltrimethylammonium bromide (DTAB), hexadecyltrimethylammonium bromide (CTAB), polyoxyethylene polyoxypropylene ether (F127), polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG).

[0047] By using the above surfactant as a complexing agent and combining it with a specific precipitant solution, the soluble metal cobalt salt can generate cobalt hydroxide with better morphology and size after precipitation reaction. Specifically, by using the above surfactant as a complexing agent, the grains can be preferentially grown on different crystal faces of cobalt hydroxide through electrostatic forces or adsorption differences of each crystal face. By adjusting the type and amount of surfactant, cobalt hydroxide with different sizes and morphologies can be obtained.

[0048] In some typical embodiments, the complexing agent includes at least one of sodium dodecyl sulfonate (SDS), hexadecyl trimethyl ammonium bromide (CTAB) and polyvinyl pyrrolidone (PVP). By using the above substances as complexing agents, it is beneficial to obtain cobalt hydroxide with better morphology and size.

[0049] Illustratively, in the complexing agent solution, the concentration of the complex can be 0.1 g / L to 100 g / L, such as 0.1 g / L, 0.5 g / L, 1 g / L, 5 g / L, 10 g / L, 20 g / L, 40 g / L, 60 g / L, 80 g / L or 100 g / L, etc., or it can be other values ​​within the range of 0.1 g / L to 100 g / L.

[0050] It should be noted that if the concentration of the complex is too high, it will be detrimental to the mass transfer and crystallization reaction of cobalt ions and hydroxide, causing the growth of the nanosheets to retard and also causing the loss of raw salt.

[0051] In some embodiments, the bottom liquid is obtained by mixing water and a liquid alkali solution; wherein the volume of water can be 30% to 70% of the volume of the reactor, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc., or other values ​​within the range of 30% to 70%. The concentration of hydroxide in the bottom liquid does not exceed 2.0 mol / L.

[0052] The conditions of the precipitation reaction include: a temperature of 30° C. to 70° C., a stirring speed of 300 rpm to 700 rpm, a hydroxide concentration in the reaction system not exceeding 2.0 mol / L, and a protective atmosphere.

[0053] The temperature of the precipitation reaction may be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc., or other values ​​within the range of 30°C to 70°C.

[0054] The precipitation reaction is carried out under stirring conditions, and the stirring speed can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm or 700rpm, etc., or other values ​​within the range of 300rpm~700rpm.

[0055] The concentration of hydroxide in the reaction system does not exceed 2.0mol / L, such as 2.0mol / L, 1.5mol / L, 1mol / L, 0.5mol / L, 0.1mol / L, 0.05mol / L, 0.01mol / L, 0.005mol / L or 0.001mol / L, etc., or other values ​​within the range of not more than 2.0mol / L and greater than 0. In some optional embodiments, the concentration of hydroxide in the reaction system can be 0.001mol / L~2.0mol / L. In some typical embodiments, the concentration of hydroxide in the reaction system is 0.02mol / L~2.0mol / L. Preferably, during the precipitation reaction, the pH value of the reaction system is not less than 11. It should be noted that the "reaction system" referred to herein is formed by all the materials in the reaction device, in other words, by the bottom liquid, the soluble cobalt salt solution, the precipitant solution and the complexing agent solution.

[0056] In some optional embodiments, a soluble cobalt salt solution, a complexing agent solution and a precipitant solution are added to the base solution in parallel, wherein the flow rate of the soluble cobalt salt solution is 1 L / h to 30 L / h (such as 1 L / h, 2 L / h, 5 L / h, 8 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h or 30 L / h, etc.), the flow rate of the complexing agent solution is 60 mL / h to 400 mL / h (such as 60 mL / h, 100 mL / h, 150 mL / h, 200 mL / h, 250 mL / h, 300 mL / h, 350 mL / h or 400 mL / h, etc.), and the precipitant solution is used to control the concentration of hydroxide in the reaction system.

[0057] In the present invention, the flow rates of the soluble cobalt salt solution and the complexing agent solution need to be controlled within the above-mentioned ratio. If the flow rate of the complexing agent solution is too large, it will be detrimental to the mass transfer and crystallization reaction of cobalt ions and hydroxide, causing the growth of the nanosheets to retard and also causing the loss of raw salt.

[0058] In some optional embodiments, the reaction atmosphere during the precipitation reaction may be a nitrogen atmosphere, an argon atmosphere, or the like.

[0059] Furthermore, the preparation process of cobalt hydroxide also includes: aging and filtering the slurry obtained from the coprecipitation reaction to form a filter cake; centrifugally washing, slurrying and drying the filter cake.

[0060] In some optional embodiments, the aging time can be 2h~6h, such as 2h, 3h, 4h, 5h or 6h.

[0061] In some optional embodiments, the centrifugal washing may include: sequentially performing alkali washing and water washing on the filter cake.

[0062] Among them, alkali washing may include the following conditions: the alkali washing temperature is 25℃~100℃ (such as 25℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃ or 100℃, etc.), the washing reagent used for alkali washing can be 1mol / L~3mol / L (such as 1mol / L, 2mol / L or 3 mol / L, etc.) of sodium hydroxide; the volume of the washing reagent used for alkali washing can be 25L~200L (such as 25L, 50L, 100L, 150L or 200L, etc.).

[0063] Water washing may include the following conditions: the water washing temperature is 70°C~100°C (such as 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, etc.), and the volume of water used for water washing can be 50L~400L (such as 50L, 100L, 150L, ​​200L, 250L, 300L, 350L or 400L, etc.).

[0064] In the filter cake after centrifugal washing, the Na content is ≤1000ppm, and the S content is ≤1000ppm.

[0065] In some optional embodiments, the slurrying time can be 0.5 h to 5 h, such as 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.

[0066] In some optional embodiments, the drying temperature may be 50° C. to 120° C., such as 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C. or 120° C., etc. Exemplarily, the material may be dried to a moisture content of ≤0.8%.

[0067] Correspondingly, the present invention also provides a cobalt hydroxide, which is prepared by the above preparation method.

[0068] The cobalt hydroxide prepared by the present invention has a nano-sheet structure. Different cobalt hydroxides prepared in the same batch are in a spatially staggered form.

[0069] In some optional embodiments, the average particle size D of the cobalt hydroxide is 50 It is 0.2μm~5μm, such as 0.2μm, 0.5μm, 1μm, 2μm, 3μm, 4μm or 5μm, and can also be other values ​​within the range of 0.2μm~5μm.

[0070] In some optional embodiments, the thickness of the cobalt hydroxide is ≤100 nm.

[0071] The spatially staggered cobalt hydroxide nanosheet structure can improve the utilization rate of active materials, improve the charge-discharge cycle life, improve the conductivity and charging efficiency of the electrode, etc. In addition, when the spatially staggered cobalt hydroxide nanosheet structure prepared by the method of the present invention is used for positive electrode materials (especially nickel-rich positive electrode materials), the electronic conductivity and rate performance of the electrode active material can be enhanced, a stable protective interface can be provided for the active material, the interface reaction between the positive electrode material and the electrolyte can be inhibited, and its cycle and service life can be improved.

[0072] In some embodiments, the cobalt hydroxide prepared by the method provided by the present invention under the same conditions can be used as a positive electrode material; in other embodiments, the cobalt hydroxide mixture of different sizes and morphologies prepared by the method provided by the present invention under different conditions can be used as a positive electrode material.

[0073] In addition, the present invention also provides a modified positive electrode material, which is obtained by coating the surface of the positive electrode material with the above-mentioned cobalt hydroxide.

[0074] In some optional embodiments, the positive electrode material may be, by way of example but not limitation, a nickel-cobalt-manganese ternary positive electrode material.

[0075] By coating the cobalt hydroxide provided by the present invention on the surface of the positive electrode material, a protective layer can be formed on the surface of the electrode material to inhibit the interface reaction between the positive electrode material and the electrolyte, and prevent the electrode from being corroded by the acidic medium, thereby stabilizing the surface structure of the material. In addition, the coating layer can also improve the ionic conductivity of the positive electrode material, promote electron transfer and lithium ion diffusion, prevent the positive electrode material from directly contacting the electrolyte, and prevent gas precipitation.

[0076] Furthermore, the present invention also provides a battery having the above-mentioned modified positive electrode material, and the battery can have higher electrochemical properties, such as specific capacity and capacity retention rate.

[0077] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0078] Example 1

[0079] This embodiment provides a method for preparing cobalt hydroxide with a particle size of 1 μm to 2 μm, comprising the following steps:

[0080] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 2 mol / L, which is referred to as solution A;

[0081] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 30%, which is referred to as solution B;

[0082] PVP was mixed with pure water to prepare a complexing agent solution with a concentration of 40 g / L, which was recorded as solution C;

[0083] S2: Add 60% pure water to the reactor, and introduce 0.4m 3 / h nitrogen as protective gas, and then start the stirring and heating program: stirring speed is 700rpm, heating to 65℃, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 0.6mol / L;

[0084] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 65°C, the stirring speed was 700 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is about 1μm~2μm. The flow rates of solution A and solution C are 20L / h and 400mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.6mol / L;

[0085] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for aging for 4 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 25L of 1mol / L sodium hydroxide at 25°C to remove excess sulfate ions; then washed with 50L of hot water at 70°C to remove excess sodium ions to obtain a sample with Na<500ppm and S<500ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0086] The SEM image of the above cobalt hydroxide product is as follows Figure 1 As shown in the figure, it can be seen that the Co(OH)2 primary particles prepared in this embodiment are large and thick flakes, and the particle uniformity is poor.

[0087] Example 2

[0088] This embodiment provides a method for preparing cobalt hydroxide with a particle size of 0.7 μm to 1 μm, comprising the following steps:

[0089] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 2 mol / L, which is referred to as solution A;

[0090] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 30%, which is referred to as solution B;

[0091] Dodecyltrimethylammonium bromide (DTAB) was mixed with pure water to prepare a complexing agent solution with a concentration of 10 g / L, which was recorded as solution C;

[0092] S2: Add 60% pure water to the reactor, and introduce 0.4m 3 / h nitrogen as protective gas, and then start the stirring and heating program: stirring speed is 700rpm, heating to 65℃, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 0.6mol / L;

[0093] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 65°C, the stirring speed was 700 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is about 0.7μm~1μm. The flow rates of solution A and solution C are 20L / h and 400mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.6mol / L;

[0094] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for aging for 4 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 25L of 1mol / L sodium hydroxide at 25°C to remove excess sulfate ions; then washed with 50L of hot water at 70°C to remove excess sodium ions to obtain a sample with Na<500ppm and S<500ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0095] That is, the preparation conditions of this embodiment differ from those of embodiment 1 in that the complexing agent is changed to dodecyltrimethylammonium bromide (DTAB), and the concentration of the complexing agent solution is 10 g / L.

[0096] The SEM image of the above cobalt hydroxide product is as follows Figure 2 As shown in the figure, it can be seen that the size of the Co(OH)2 primary particles prepared in this embodiment is smaller than that in Example 1, and the area of ​​the Co(OH)2 primary particles is smaller and the thickness is thinner.

[0097] Example 3

[0098] This embodiment provides a method for preparing cobalt hydroxide with a particle size of 0.5 μm to 0.7 μm, comprising the following steps:

[0099] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 2 mol / L, which is referred to as solution A;

[0100] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 30%, which is referred to as solution B;

[0101] Sodium dodecyl sulfate was mixed with pure water to prepare a complexing agent solution with a concentration of 2 g / L, which was recorded as solution C;

[0102] S2: Add 60% pure water to the reactor, and introduce 0.4m 3 / h nitrogen as protective gas, and then start the stirring and heating program: stirring speed is 700rpm, heating to 65℃, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 0.6mol / L;

[0103] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 65°C, the stirring speed was 700 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is about 0.5μm~0.7μm. The flow rates of solution A and solution C are 20L / h and 400mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.6mol / L;

[0104] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for aging for 4 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 25L of 1mol / L sodium hydroxide at 25°C to remove excess sulfate ions; then washed with 50L of hot water at 70°C to remove excess sodium ions to obtain a sample with Na<500ppm and S<500ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0105] That is, the preparation conditions of this embodiment differ from those of embodiment 1 in that the complexing agent is changed to sodium dodecyl sulfate, and the concentration of the complexing agent solution is 2 g / L.

[0106] The SEM image of the above cobalt hydroxide product is as follows Figure 3 As shown in the figure, it can be seen that the size of the Co(OH)2 primary particles prepared in this embodiment is smaller than that in Example 1, the area of ​​the Co(OH)2 primary particles is smaller and the thickness is thinner, and the uniformity of the Co(OH)2 primary particles is better.

[0107] Example 4

[0108] This embodiment provides a method for preparing cobalt hydroxide with a particle size of 0.3 μm to 0.5 μm, comprising the following steps:

[0109] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 2 mol / L, which is referred to as solution A;

[0110] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 30%, which is referred to as solution B;

[0111] Hexadecyltrimethylammonium bromide (CTAB) was mixed with pure water to prepare a complexing agent solution with a concentration of 10 g / L, which was recorded as solution C;

[0112] S2: Add 60% pure water to the reactor, and introduce 0.4m 3 / h nitrogen as protective gas, and then start the stirring and heating program: stirring speed is 700rpm, heating to 65℃, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 0.6mol / L;

[0113] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 65°C, the stirring speed was 700 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is about 0.3μm~0.5μm. The flow rates of solution A and solution C are 20L / h and 400mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.6mol / L;

[0114] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for aging for 4 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 25L of 1mol / L sodium hydroxide at 25°C to remove excess sulfate ions; then washed with 50L of hot water at 70°C to remove excess sodium ions to obtain a sample with Na<500ppm and S<500ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0115] That is, the preparation conditions of this embodiment differ from those of embodiment 1 in that the complexing agent is changed to hexadecyltrimethylammonium bromide (CTAB), and the concentration of the complexing agent solution is 10 g / L.

[0116] The SEM image of the above cobalt hydroxide product is as follows Figure 4 As shown in the figure, it can be seen that the size of the Co(OH)2 primary particles prepared in this embodiment is smaller than that of Examples 1 to 3, the area of ​​the Co(OH)2 primary particles is smaller and the thickness is thinner, and the uniformity of the Co(OH)2 primary particles is better.

[0117] Example 5

[0118] The difference between this embodiment and embodiment 1 is that the concentration of the complexing agent solution is 80 g / L.

[0119] The remaining preparation conditions are the same as those in Example 1.

[0120] The morphology of the cobalt hydroxide product prepared in this example is as follows Figure 5 As shown in the figure, it can be seen that changing the concentration of PVP within the range provided by the present invention will not have a significant effect on the size of the cobalt hydroxide particles, and the particle size of the cobalt hydroxide product obtained in this embodiment is also 1 μm~2 μm.

[0121] Example 6

[0122] The difference between this embodiment and embodiment 2 is that the concentration of the complexing agent solution is 0.1 g / L.

[0123] The remaining preparation conditions are the same as those in Example 2.

[0124] The morphology of the cobalt hydroxide product prepared in this example is as follows Figure 6As shown in the figure, it can be seen that changing the concentration of DTAB within the range provided by the present invention will not have a significant effect on the size of the cobalt hydroxide particles, and the particle size of the cobalt hydroxide product obtained in this embodiment is also 0.7 μm~1 μm.

[0125] Example 7

[0126] This embodiment provides a method for preparing cobalt hydroxide, comprising the following steps:

[0127] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 1 mol / L, which is referred to as solution A;

[0128] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 10%, which is referred to as solution B;

[0129] CTAB was mixed with pure water to prepare a complexing agent solution with a concentration of 7.5 g / L, which was recorded as solution C;

[0130] S2: Add 30% pure water to the reactor, and introduce 0.4m 3 / h argon as protective gas, and then start the stirring and heating program: stirring speed is 300rpm, heating to 30°C, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 2mol / L;

[0131] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 30°C, the stirring speed was 300 rpm, and 0.4 m 3 / h argon gas was used as protective gas, and the reaction was continued until the product particle size was about 0.6μm~1.0μm. The flow rates of solution A and solution C were 1L / h and 60mL / h respectively, and the flow rate of solution B was used to control the hydroxide concentration in the reaction system to 2mol / L;

[0132] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for aging for 2 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 100L of 2mol / L sodium hydroxide at 50°C to remove excess sulfate ions; then washed with 200L of hot water at 80°C to remove excess sodium ions to obtain a sample with Na<100ppm and S<1000ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0133] Example 8

[0134] This embodiment provides a method for preparing cobalt hydroxide, comprising the following steps:

[0135] S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 3 mol / L, which is referred to as solution A;

[0136] Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 50%, which is referred to as solution B;

[0137] PVP was mixed with pure water to prepare a complexing agent solution with a concentration of 40 g / L, which was recorded as solution C;

[0138] S2: Add 70% pure water to the reactor, introduce 0.4m3 / h nitrogen as protective gas, and start stirring and heating procedures: stirring speed is 500rpm, heating to 70°C, and then adding liquid alkali to adjust the hydroxide concentration in the bottom liquid to 0.02mol / L;

[0139] S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 70°C, the stirring speed was 500 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is about 0.6μm~1.0μm. The flow rates of solution A and solution C are 30L / h and 200mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.02mol / L;

[0140] S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for 6 hours, and then pumped to a centrifuge to form a filter cake after drying. The filter cake is then alkaline washed with 200L of 3mol / L sodium hydroxide at 100°C to remove excess sulfate ions; then washed with 400L of hot water at 100°C to remove excess sodium ions to obtain a sample with Na<100ppm and S<1000ppm; the sample is then dried and mixed to obtain a cobalt hydroxide product.

[0141] Comparative Example 1

[0142] The difference between this comparative example and Example 4 is that the complexing agent replaces the most common ammonia solution in the precursor synthesis, and its concentration is 4 g / L.

[0143] The morphology of the cobalt hydroxide product prepared in this comparative example is as follows Figure 7 As shown in the figure, it can be seen that when synthesized using the traditional method, the morphology of the cobalt hydroxide particles will change significantly, showing thin and long sheets, and the distribution of the particles is uneven. The particle size of the cobalt hydroxide product obtained in this comparative example is also 1μm~2μm.

[0144] Test example

[0145] The cobalt hydroxide prepared in Examples 1 to 6 and Comparative Example 1 was physically mixed with NCM positive electrode materials (Ni:Co:Mn=92:4:4 in molar ratio) and annealed at 770° C. to prepare different modified positive electrode materials.

[0146] The above modified positive electrode materials were mixed into slurry according to the ratio of modified positive electrode material: conductive carbon: polyvinylidene fluoride (PVDF) = 90:5:5 to make positive electrode sheets (the compaction density of the sheet is 3.3g / cm 2 ), metal lithium sheet was selected as the negative electrode material and assembled into a CR2025 button battery.

[0147] Using 1 mol / L LiPF6 / EC:DEC:DMC=1:1:1 (V%) as the electrolyte (EC is ethylene carbonate, DEC is diethyl carbonate, and DMC is dimethyl carbonate), after 3 cycles at 0.1C rate, the discharge capacity retention rate of the button cell was obtained by cycling 100 times at 1C rate. Among them, the charging voltage is 4.3V, and the capacity retention rate (%) after 100 cycles = discharge capacity at the 100th cycle / discharge capacity at the 1st cycle × 100%. The test results are shown in Table 1.

[0148] Table 1 Test results

[0149]

[0150] It can be seen from Examples 1 to 4 in Table 1 that the modified positive electrode materials obtained by coating the positive electrode materials with cobalt hydroxides of different sizes have different effects on the battery cycle performance.

[0151] It can be seen from the results of Examples 1 to 6 and Comparative Example 1 that the cobalt hydroxide prepared by the preparation method provided by the embodiment of the present invention can improve the capacity cycle retention rate of the positive electrode material more than the cobalt hydroxide prepared in the comparative example.

[0152] In summary, the preparation method of cobalt hydroxide provided by the present invention is simple to operate, the process is easy to control, and by regulating the surfactant, cobalt hydroxide of different sizes and unique spatially staggered nanosheet structures can be obtained, which is beneficial to improving the utilization rate of active materials, improving the charge and discharge cycle life, improving the conductivity and charging efficiency of the electrode, etc. Using it as a coating can improve the thermal stability and structural stability of the positive electrode material, inhibit the interface reaction between the positive electrode material and the electrolyte, and thus enhance its cycle stability.

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified positive electrode material, characterized in that: The modified positive electrode material is obtained by coating the surface of the positive electrode material with cobalt hydroxide nanosheets; The preparation of the cobalt hydroxide comprises the following steps: S1: Dissolve cobalt sulfate in pure water to prepare a cobalt sulfate solution with a concentration of 2 mol / L, which is referred to as solution A; Mix solid sodium hydroxide with water to prepare a precipitant solution with a concentration of 30%, which is referred to as solution B; Mix hexadecyltrimethylammonium bromide and pure water to prepare a complexing agent solution with a concentration of 10 g / L, which is referred to as solution C; S2: Add 60% pure water to the reactor, and introduce 0.4m 3 / h nitrogen as protective gas, and then start the stirring and heating program: stirring speed is 700rpm, heating to 65℃, and then adding liquid alkali to adjust the hydroxide concentration in the base liquid to 0.6mol / L; S3: Solution A, solution B and solution C were simultaneously pumped into the reactor of S2 in parallel to perform precipitation reaction; the reaction temperature was maintained at 65°C, the stirring speed was 700 rpm, and 0.4 m 3 / h nitrogen as protective gas, and react until the product particle size is 0.3μm~0.5μm; the flow rates of solution A and solution C are 20L / h and 400mL / h respectively, and the flow rate of solution B is used to control the hydroxide concentration in the reaction system to 0.6mol / L; S4: The slurry obtained by the coprecipitation reaction is placed in an aging kettle for 4 hours, and then pumped to a centrifuge to form a filter cake after drying, and then the filter cake is alkaline washed with 25L of 1mol / L sodium hydroxide at 25°C to remove excess sulfate ions; and then washed with 50L of hot water at 70°C to remove excess sodium ions to obtain a sample with Na<500ppm and S<500ppm; and then the sample is dried and mixed to obtain a cobalt hydroxide product; The particle size of the cobalt hydroxide nanosheet product is 0.3 μm to 0.5 μm.

2. A battery, characterized in that: The battery comprises the modified positive electrode material according to claim 1.

Citation Information

Patent Citations

  • Method for continuously preparing cobalt hydroxide with high bulk density

    CN103342394A

  • Preparation method of beta-type mesoporous cobalt hydroxide and application of beta-type mesoporous cobalt hydroxide in electroreduction of carbon dioxide

    CN116575061A

  • Nano cobalt hydroxide as well as preparation method and application thereof

    CN117794864A